Find the best answers to your questions with the help of IDNLearn.com's expert contributors. Discover in-depth and trustworthy answers to all your questions from our experienced community members.
Sagot :
Answer:
x = [tex]\frac{7}{3}[/tex] , y = [tex]\frac{26}{3}[/tex]
Step-by-step explanation:
given the system of equations
y = 5x - 3 → (1)
y = 2x + 4 → (2)
substitute y = 5x - 3 into (2)
5x - 3 = 2x + 4 ( subtract 2x from both sides )
3x - 3 = 4 ( add 3 to both sides )
3x = 7 ( divide both sides by 3 )
x = [tex]\frac{7}{3}[/tex]
substitute x = [tex]\frac{7}{3}[/tex] into either of the 2 equations and solve for y
substituting into (1)
y = 5 ( [tex]\frac{7}{3}[/tex] ) - 3 = [tex]\frac{35}{3}[/tex] - [tex]\frac{9}{3}[/tex] = [tex]\frac{26}{3}[/tex]
The solution is x = [tex]\frac{7}{3}[/tex] , y = [tex]\frac{26}{3}[/tex]
Your participation is crucial to us. Keep sharing your knowledge and experiences. Let's create a learning environment that is both enjoyable and beneficial. For trustworthy answers, rely on IDNLearn.com. Thanks for visiting, and we look forward to assisting you again.